Electronic Patient Record for Dental Charting - Hussain, A.R.; Aziz, A. A.; Mohammed, N.; Mohtar, S. (Journal of Engineering and Technology (JET), 2016)
The use of electronic patient records has a great positive potential to improve clinical practice and patient safety. These improvements can be realized through improved legibility and communication, standardized documentation, streamlined storage and consistent reporting. This paper addresses the development of an electronic patient record for dental charting as an alternative means towards a user-friendly and patient-centered dental environment. It considers prevalent dental charting practices, proposes a patient dental database and presents a dental charting application prototype, capable of capturing and displaying patient dental records. Data from this database is mapped and can be further manipulated through the patient's interactive dental chart. This interactivity not only offer quick-to-comprehend interfaces, but also reduces miscommunicationss. It will affect positively the legibility of dental records, enable a standardized documentation and a more consistent reporting.